2015
DOI: 10.1007/s40615-015-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Chronic Pain and Quality of Life among Adolescents and Young Adults with Moderate or Severe Hemophilia

Abstract: Background and ObjectiveWe explored racial differences in adherence to recommended clotting factor treatment regimens, chronic pain, and quality of life (QoL) among adolescents and young adults (AYAs) diagnosed with moderate or severe hemophilia.MethodsA convenience sample of hemophilia patients aged 13–25 years completed an online cross-sectional survey in 2012. Chronic pain was measured using the revised Faces Pain Scale (FPS-R) and dichotomized as high (FPS-R ≥ 4) or low (FPS-R < 4). QoL was measured with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
(60 reference statements)
2
10
0
Order By: Relevance
“…Findings of our study are consistent with McLaughlin et al (2016) who reported that racial differences in chronic pain level accounted for statistically different QOL scores between Whites and non-Whites (comparison between Latino/Hispanic and non-Latino/Black was not reported). McLaughlin et al (2016) examined the relationship between race, adherence, chronic pain, and QOL in a sample of 80 adolescents and young adults with hemophilia where the sample was 61% White (12% Hispanic and 88% non-Hispanic) and 19% non-White (14% Hispanic and 86% non-Hispanic).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Findings of our study are consistent with McLaughlin et al (2016) who reported that racial differences in chronic pain level accounted for statistically different QOL scores between Whites and non-Whites (comparison between Latino/Hispanic and non-Latino/Black was not reported). McLaughlin et al (2016) examined the relationship between race, adherence, chronic pain, and QOL in a sample of 80 adolescents and young adults with hemophilia where the sample was 61% White (12% Hispanic and 88% non-Hispanic) and 19% non-White (14% Hispanic and 86% non-Hispanic).…”
Section: Discussionsupporting
confidence: 92%
“…Findings of our study are consistent with McLaughlin et al (2016) who reported that racial differences in chronic pain level accounted for statistically different QOL scores between Whites and non-Whites (comparison between Latino/Hispanic and non-Latino/Black was not reported). McLaughlin et al (2016) examined the relationship between race, adherence, chronic pain, and QOL in a sample of 80 adolescents and young adults with hemophilia where the sample was 61% White (12% Hispanic and 88% non-Hispanic) and 19% non-White (14% Hispanic and 86% non-Hispanic). McLaughlin et al (2016) reported that scores for non-Whites were significantly lower than those for Whites on Physical Composite Summary Score ( p = .02), and on Bodily Pain subscale ( p = .02), Physical Function subscale ( p = .03), and Role Limitations subscale ( p = .01).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As the name suggests, the IMPACT QoL study had the primary goal of assessing the relationship between validated measures of pain, clotting-factor adherence, and HRQoL among AYA PWH or VWD. Data describing the relationship between adherence to a prescribed clotting factor treatment regimen and chronic pain, along with racial differences in chronic pain and QoL from this study, were previously reported [24, 25]. Data were collected via a one-time, cross-sectional, online survey from a convenience sample of AYA PWH or VWD.…”
Section: Methodsmentioning
confidence: 99%
“…Out of 16 studies, 12 reports mentioned identifying the factors or correlates of adherence as their primary or secondary objectives. More than two thirds of studies (11/16) adopted a cross-sectional data collection including those with retrospective data from chart review, 29 , 30 , 32 , 33 , 35 , 36 , 39 , 40 , 42 whereas two were pre-post evaluations of interventions. 31 , 41 Two had prospective follow-up designs, 34 , 37 and one was a qualitative inquiry on the experience of treatment in adults.…”
Section: Results: Prophylaxis Treatment In Hemophiliamentioning
confidence: 99%